PENGARUH MINAT BACA DAN PENGUASAAN KOSAKATA TERHADAP PRESTASI BELAJAR BAHASA INGGRIS - Eva Novianti (INFERENCE: Journal of English Language Teaching, 2019)
This current study aims to determine: 1) The effects of interest in reading and vocabulary mastery together towards English learning achievement. 2) The Effect of interest in reading English learning achievement. 3) The Effect of vocabulary mastery towards English learning achievement. The method used surveys, the observed population of this research is students from state senior high schools in Districts Tangerang. The 88 samples were gained through cluster proportional and random sampling. The analysis used is multiple linear regression. The results of the study show: 1) there are significant effects of interest in reading and vocabulary mastery altogether towards English learning achievement.  It is proved by Sig.= 0.000 < 0.05 and Fobserved = 9.063; 2). There is a significant effect of interest in reading towards English learning achievement. It is proved by Sig.= 0.005 < 0.05 and tobserved = 2.865; 3) There is a significant effect of vocabulary mastery towards English learning achievement. It is proved by Sig.= 0.000 < 0.05 and tobserved = 4.206. Key Words: reading interest; vocabulary mastery; English learning achievement